Analysis of Serum and Salivary Lipid Profile in Control Subjects and Diabetic Patients–A Comparative Study - Arunachalam, Nirmala; Sultana, Mazher (Asian Journal of Biological and Life Sciences)
Patients with diabetes mellitus have a greater risk of dyslipidaemia. Abnormalities in lipid metabolism have been shown to be key risk factors for the development of diabetes-related complications. Lipids are the critical biomolecules for pathological and physiological processes in the human body and their examination is essential for diagnosing health and disease conditions such as diabetes mellitus, atherosclerosis and related complications. The objective of this study was to ascertain the diagnostic potential of saliva in the assessment of lipid profile as compared to that of serum lipid profile. The selected study area of Thiruporur conducted a Diabetic camp to collect the samples from 200 control subjects and 200 Type - II diabetic patients from different age groups. Total Cholesterol (TC), High-Density Lipoprotein (HDL), Triglycerides (TG), Low-Density Lipoprotein (LDL), Very Low-Density Lipoprotein (VLDL), and the ratio of Total Cholesterol to High- Density Lipoprotein (TC/HDL) were analysed in the serum and saliva of the diabetic patients and the control subjects. When compared to the control group, patients with Type II diabetes have an abnormal blood lipid profile with elevated TC (246.8253.48mg/dl), high LDL (156.6253.484mg/dl), VLDL (42.36510.99mg/dl), TG (211.833 54.97 mg/dl), and TC/HDL ratio (5.471 1.239), but inadequate HDL (45.2793.199 mg/dl) levels were observed. According to the findings of this study, an increase in serum lipid profile values and corresponding increases in saliva lipid profile values were also observed. As per the outcome of the present study, saliva can be utilised as a non-invasive diagnostic tool for measuring lipid profile in diabetic patients
Keywords: cholesterol; Diabetes mellitus; Lipid profile; Salivary Biomarkers; Salivary Lipid profile